UTILIZATION OF FLASH CARDS AS A VOCABULARY AND CONCEPT LEARNING MEDIA FOR ELEMENTARY SCHOOL STUDENTS - reza zauliyah (Teaching and General Education Studies, 2026)
Flashcards, or picture cards, are a visual learning medium widely used in elementary schools. They are useful for helping students understand vocabulary and learning concepts in a medium for learning vocabulary and concepts for elementary school students based on a literature review. The method used is library research, analyzing various sources such as books, scientific journals, and relevant research findings. The results of the study indicate that the use of flashcards can improve memory, conceptual understanding, learning motivation, and active student participation in the learning process. Furthermore, flashcards are also effective for use in thematic learning because they are flexible and easily adapted to various materials. Thus, Flashcards can be an innovative and effective alternative learning medium to support the teaching and process in elementary schools.